Lunar effect : analysis on emerging countries stock returns, prior and during financial crisis / Nur Liyana Mohamed Yousopa, Zuraidah Sipon and Carolyn Soo Kum Yokec. - Mohamed Yousopa, Nur Liyana; Sipon, Zuraidah; Soo Kum Yokec, Carolyn (UiTM Press, 2014)
The random walk hypothesis is a theory which states that market prices are not influenced by prior price movements and therefore, prices in the stock market cannot simply be predicted. The stock market is considered efficient and follows the random walk theory when intelligent market participants lead the situation and reflect all available information based on the past or future events. The phenomena of calendar anomalies in stock markets are proven from the previous study, where behavior of returns tend to be high or low during specific calendar periods. Thus, for this study, we aims to investigate relationships between lunar effect and average stock returns for ten emerging countries for the period of January 2004 until December 2010. A lunar effect is a phenomenon where mean returns around the new moon is higher than mean returns around the full moon. Using non-parametric and basic multiple linear regression analysis, the result shows that returns on the full moon were slightly lower as compared to the returns on the new moon prior to the financial crisis and vice versa during the financial crisis.